Avaliação normativa da implantação do Método Canguru na maternidade de Odete Valadares, Belo Horizonte, Minas Gerais - Tarcisio Laerte Gontijo (2006)
New born´s low weight and the high children mortality rates result in serious problems for thehealth system in our country. All over the world twenty million children are born underweight andpremature yearly. Among them, 40% die before reaching one year of age. One of the main causesof mortality is the low quality of the assistance given to these children. In developing countriesthere is a lack of hospitals with suitable infra-structure and resources to give the necessaryassistance. As an alternative of assistance to these children, it was created in Colombia, theKangaroo Mother Program, which consists of the touch between mother and child. In Brazil, since1999, the Health Office (Ministério da Saúde MS) has been working to implant and consolidatethis methodology, including it in the political guidelines of attention to the health of low-weightedborn children and prematures, with the creation of the Humanization Program to Pre-natal andLabor. The extension of the implantation, its adaptation to the rules of the Health Office, theability to deal with the methodology, the results at local level are aspects not very well known yet.However, the goal of this work was to evaluate the implantation of the Kangaroo Mother Methodat Maternity Odete Valadares, comparing it with the one recommended by the Health Office inRules for the Humanized Attention to Low-Weighted New Borns. It is about the study ofevaluation based in classic aspects of normative evaluation: structure, process and result. Thequalitative methodology was adopted to analyze the interviews and the following assessmentpoints were identified: a) Understanding of the proposal by the team, b) adaptation of the servicesto the needs of clients, c) level of satisfaction concerning care, d) Interaction of mothers with theteam/service, e) Access to services and f) Valorization of the proposal by the institution. Theresults allow us to conclude that the Kangaroo Mother Method at Maternity Odete Valadares wasimplanted by leadership and protagonism of some professionals. There was not a prioritization ofthe project by the Institution, which generated obstacles such as low level of involvement and qualification of the team and disarticulation of the three stages. The service is well evaluated bymothers who feel safer in taking care of the premature baby.